Academic advising and student support: Help-seeking behaviors among Saudi dental undergraduate students - Asim Al-Ansari; Maha El Tantawi; Maha AbdelSalam; Fahad Al-Harbi (Elsevier, 2015)
Objective: The purpose of this study was to assess the use of and satisfaction with the academic-advising and student-support systems available to undergraduate students in the College of Dentistry at the University of Dammam. In addition, the study aimed to also identify factors that explained the help-seeking behavior of students which they used to solve academic issues. Materials and methods: Students enrolled in the five-year Bachelor of Dental Surgery (BDS) program in 2012-13 and 2013-14 first-year students were invited to respond to a self-administered questionnaire. Results: The results showed that 66.2% of students had discussed academic issues with their advisor at least once, with a frequency ranging from zero to six times. Most students reported that their advisors were readily available, listened intently to their needs and questions, and helped them solve their problems. However, only 7.6% of students relied primarily on advisors for help with academic issues, whereas 51% depended first on colleagues and 13.8% did not seek help and relied on themselves. In total, 17.2% of students were very or somewhat satisfied with the academic advising system. Males had lower odds of discussing issues with their advisors, and the odds were higher with advisors who were more available (OR = 0.25 and 3.74, respectively). Alerting students to important dates in the academic calendar significantly increased the odds that a student would depend primarily on academic advisors for advice related to academic issues (OR = 6.53). Conclusions: Few students were satisfied with the academic support system. We need to train advisors to help them develop their skills and knowledge and to enable them to provide the support needed by the students. Keywords: Undergraduate dental students, Academic advising, Student support, Academic performance